1998
DOI: 10.1172/jci2117
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor administration to HIV-infected subjects augments reduced leukotriene synthesis and anticryptococcal activity in neutrophils.

Abstract: Neutrophil (PMN) dysfunction occurs in HIV infection. Leukotrienes (LT) are mediators derived from the 5-lipoxygenase (5-LO) pathway that play a role in host defense and are synthesized by PMN. We investigated the synthesis of LT by PMN from HIV-infected subjects. There was a reduction (4.0 Ϯ 1.3% of control) in LT synthesis in PMN from HIV-infected compared with normal subjects. This was associated with reduced expression of 5-LO-activating protein (31.2 Ϯ 9.6% of normal), but not of 5-LO itself. Since HIV do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 44 publications
2
65
2
1
Order By: Relevance
“…Whether LTB 4 could be a useful immunostimulant for the treatment of infectious diseases remains to be investigated in clinical trials; numerous animal studies have already reported a beneficial effect of this eicosanoid models of infection (57)(58)(59)(60)(61)(62)(63)(64). LTB 4 administration to humans has been documented (29,65,66), with pharmacodynamic effects (␣-defensin and MIP-1␤ release (29) and PMN count variations (our unpublished data)) similar to what is reported in this study in monkeys without significant adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether LTB 4 could be a useful immunostimulant for the treatment of infectious diseases remains to be investigated in clinical trials; numerous animal studies have already reported a beneficial effect of this eicosanoid models of infection (57)(58)(59)(60)(61)(62)(63)(64). LTB 4 administration to humans has been documented (29,65,66), with pharmacodynamic effects (␣-defensin and MIP-1␤ release (29) and PMN count variations (our unpublished data)) similar to what is reported in this study in monkeys without significant adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, peripheral blood PMN (58,69), monocytes (70), and alveolar macrophages (71) from HIV-1-infected subjects have a profound defect in their capacity to produce leukotrienes. This deficit translates into the improper in vitro killing of microbes but can be overcome by G-CSF administration to HIV-1-infected subjects and the concomitant restoration of leukotriene biosynthesis potential (58).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their originally recognized roles in myelopoiesis, G-CSF and GM-CSF are also recognized to up-regulate leukocyte functional responses, such as the recruitment, survival, phagocytosis, and microbicidal activities of neutrophils, monocytes, and macrophages (63). A role in LT synthesis is demonstrated by the facts that macrophages from GM-CSF-deficient mice exhibit reduced LT synthesis (64), and exogenous addition of CSFs has been shown to enhance the capacity for LT biosynthesis in vitro (65,66) and in vivo (49,67). Nitric oxide.…”
Section: Modulation Of Lt Synthesis By Other Mediators Of Innate Immumentioning
confidence: 99%
“…HIV infection. Peripheral blood neutrophils (49,78), monocytes (67), and alveolar macrophages (79) from patients with HIV infection have all been reported to manifest a profound defect in their capacity for stimulated LT generation. This defect was confined to the 5-LO pathway and was associated with reduced expression of 5-LO and FLAP.…”
Section: Lt Deficiency In States Of Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation